Risk Factors for Dental Caries in Elementary School Children Aged 6-12 in Indonesia (Systematic Literatur Review) - Rahatina, Vilianti Eka Fitri; Hadisaputro, Suharyo; Setyawan S, Henry (Poltekkes Kemenkes Semarang, 2023)
Background: The highest prevalence of dental caries was in the group of children aged 5-9 years (92.6%), and in the age group 3-4 years was 81.1%. Unhealthy teeth and mouth can affect a child's development because the condition of the milk teeth will determine the growth of the child's permanent teeth. Caries are influenced by brushing teeth, how to brush teeth, consumption of cariogenic foods, knowledge, and possibly many other factors that can affect caries. Purpose: to review the collected literature on risk factors for dental caries in children aged 6-12 years in Indonesia. Methods: This study used the literature review method which began with searching research results in 3 databases, namely PubMed, ScienceDirect, and Google Scholar with predetermined inclusion criteria. Results: The articles that have been obtained in this literature show that there are many variables in the process of dental caries in elementary school children in Indonesia. These variables are divided into several discussion groups, namely individual characteristics, parental characteristics, consumption patterns, dental and oral hygiene, socioeconomic status, and dental and oral health interventions. Conclusion: there are many variables selected to be risk factors for dental caries, but not all variables are proven to be risk factors for dental caries in elementary school children. This is because other factors make the hypothesis rejected.